'Roșia Montană, the revolution of our generation': from environmental to total activism. Issue 2 (15th March 2021) - Soare, Sorina; Tufiș, Claudiu D.
ABSTRACT: We analyse Roșia Montană environmental activism as a critical case that brings together an unusual combination of high levels of transactional activism and high levels of mass protests. We build on the assumptions of civil society in post-communist Europe and the literature on environmental mobilization to investigate the ways in which environmental-based activism developed before and after Romania's accession to the European Union (EU). Starting from the consensual interpretation of the indirect contribution the EU had in reinforcing the space of manoeuvring and the legitimacy of the pre-2007 Roșia Montană activism, we show that the post-accession period corresponds to an ongoing civil society empowerment despite the state actors' strong resistance to open policy processes. Roșia Montană activism proves that, under certain conditions, the political actors can lose the total exclusivity in the policy-making in favour of more or less organized actors.